2017
DOI: 10.21521/mw.5751
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aleutian mink disease in selected national mink farms in light of serological and molecular investigations

Abstract: The aim of the study was to evaluate the prevalence of seroreagents to Aleutian mink disease virus (AMDV) in minks. Sera samples from 1233 minks were tested by CIEP. The antibodies against AMDV were not found in the mink farms which continued the AMD eradication program. In farms where the eradication program had not been implemented a bad epizootic situation was detected. The percentage of seroreagents between 33.3% and 97.8% was noticed: in females 33.3% to 91.8% whereas in males it ranged from 61.5% to 97.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Farms where the programme was implemented very early have not recorded AMDV. The virus prevalence reached 70% on farms where the programme was implemented a few years before the study and 93% on farms that had not implemented the programme (Siemionek et al., 2017 ). However, these data come from only 6 farms and there is no information how many farms in Poland (from about 360) implemented this programme.…”
Section: Discussionmentioning
confidence: 99%
“…Farms where the programme was implemented very early have not recorded AMDV. The virus prevalence reached 70% on farms where the programme was implemented a few years before the study and 93% on farms that had not implemented the programme (Siemionek et al., 2017 ). However, these data come from only 6 farms and there is no information how many farms in Poland (from about 360) implemented this programme.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the AMDV variants that infected both farmed and free-ranging minks could have originated from a common source but split into two separate subgroups that can be identified based on their distinctive characteristics [35]. In 2017, Siemionek et al relied on CIEP and PCR assays to assess the epidemiological status of mink farms [52]. PCR was performed based on the protocol that was previously described by Oie et al [19].…”
Section: Molecular Epidemiology Of the Amdvmentioning
confidence: 99%
“…no. KT203355-KT203365) [52]. The epidemiological status of 27 mink farms in seven Polish voivodeships was also investigated in 2019 by Kowalczyk et al [53].…”
Section: Molecular Epidemiology Of the Amdvmentioning
confidence: 99%